IMPLEMENTASI REGULASI TENTANG PENINGKATAN HAK GUNA BANGUNAN ( HGB ) MENJADI HAK MILIK ( HM ) UNTUK RUMAH TEMPAT TINGGAL DI KOTA SEMARANG - Wienda Dhamesti*, Ana Silviana, Sukirno (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2014)
Article 1 verse 1 decision of the minister of agrarian affairs / head of national land agency No. 6 1998, concering the granting of property rights over land to home living. The purpose of this research is to find out and analyse the implementation of the regulation about the improvement of building use rights to households and dwellings into property rights in the Semarang city. And the obstacles encountered in the ground for adwelling house. The approach method used in this research is the empirical juridical research, specification research is descriptive analytical. A method of analysis of data used are qualitative analysis method. From the research found that implementation has some constraints. the first in the applicant’s right to make omprovements often lacking understanding of the process, cost, and condition. the second minimum coorperation between National Land Agency and neighborhood parties, and the last, yhe applicant was less active in supplementing the terms needed in the improvement of land rights. Esults of the research implementation regulation of building use rights over the land to become residential property in Semarang City based on the decisionof the mnister of agrarian affairs / head of national land agency No. 6 1998, concerning the grant rights belonging to the ground for residence. Is good and smoothly run by communities in the city of Semarang, for there are many people raise the status of home addresess of the beneficial building become their property and they improve it before its term has exhausted. Althought there are still some problems / deficient in implementation. Il have been done by following the procedurere gardimg the improvement of the prevalling land rights. Keyword : The Implementation Of Improved Building Use Rights Into Property Rights